Grundrecht auf selbstbestimmtes Sterben Verfassungsrechtliche Grundlagen und schutzgutsimmanentes Freiverantwortlichkeitskonzept - Remé, Johann (Mohr Siebeck, 2025)
Johann Remé analyses the right to self-determined death under the German Basic Law. He develops a concept of free will as an intrinsic condition of this fundamental right. In this context, he substantiates an obligation of the legislature to define free will and explores the constitutional requirements for such a concretisation.
PublicationDate: 20250318
Keywords: Tod -- Allgemeines Persönlichkeitsrecht -- Autonomie -- Ausgestaltung von Grundrechten -- Grundrechtsausgestaltung -- Schutzpflicht -- Verfassungsrecht und Staatslehre